2015
DOI: 10.1103/physrevb.92.014108
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous crystal nucleation in liquid copper under quasi-isentropic compression

Abstract: Shock-induced freezing in liquids has long been a subject of interest as well as mystery. With large-scale molecular dynamics simulations, we demonstrate that homogeneous crystal nucleation in liquid Cu can be realized under certain supercooling (θ), via quasi-isentropic compression or ramp wave loading with a particle velocity u p achieved within a ramp time τ . The simulations yield the τ -u p -θ relations for homogeneous crystallization at the spatial and temporal scales of molecular dynamics; a ramp wave l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…We also showed that the matter constituents change significantly with the finite isospin chemical potentials. In asymmetric matter, ∆ − appears first similarly to the ones obtained in the neutron star analyses [15][16][17][18].…”
Section: Summary and Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…We also showed that the matter constituents change significantly with the finite isospin chemical potentials. In asymmetric matter, ∆ − appears first similarly to the ones obtained in the neutron star analyses [15][16][17][18].…”
Section: Summary and Discussionsupporting
confidence: 52%
“…In this N -∆ matter, the effective masses of ∆ and N are close to each other as in Eq. (17). Since ∆ has sixteen degrees of freedom (spin 3/2 and isospin 3/2) compared with four (spin 1/2 and isospin 1/2) for nucleon, the ∆ density could be larger than N density.…”
Section: Delta Mattermentioning
confidence: 99%
See 2 more Smart Citations
“…Although only two cases, that is, cavitation of LJ and Cu liquids, are considered here, the equivalence between temporal and spatial scales is likely common for any physical processes that involve nucleation of a new "phase" and hence should apply to a variety of processes for many materials, including chemical reactions, plasticity, melting and crystallization. 47 Equation 6 is quite general and can be used to make upward or downward extrapolations from one scale to another, either in time or in space.…”
Section: The Journal Of Physical Chemistry Lettersmentioning
confidence: 99%